Pengaruh Inovasi Produk dan Persepsi Harga terhadap Loyalitas Pelanggan di KKV dengan Kepuasan Pelanggan sebagai Variabel Intervening - Lulu Septiana; Edy Purwo Saputro (El-Mal: Jurnal Kajian Ekonomi & Bisnis Islam, 2025)
This study aims to analyze the effect of product innovation and price perception on customer loyalty, with customer satisfaction as an intervening variable at the KKV retail store. The method used is a quantitative approach by distributing questionnaires to 130 respondents who are students of the Muhammadiyah University of Surakarta and the general public who have shopped at KKV. Data were analyzed using the Partial Least Square - Structural Equation Modeling (PLS-SEM) method with the help of SmartPLS software. The results of the study indicate that product innovation and price perception have a positive and significant effect on customer satisfaction. In addition, price perception has a greater influence on customer loyalty than product innovation. Customer satisfaction is also proven to be a mediating variable that strengthens the relationship between product innovation and price perception on customer loyalty. This study provides theoretical and practical contributions in understanding strategies that can increase customer loyalty through innovation and price management.